Modulating the gut microbiota ameliorates spontaneous seizures and cognitive deficits in rats with kainic acid-induced status epilepticus by inhibiting inflammation and oxidative stress - Wang, Xue; Yang, Chunyu; Yang, Liu; Zhang, Yongbo (Frontiers in Nutrition, 2022)
Introduction: Epilepsy is a highly prevalent neurological disease whose treatment has always been challenging. Hence, it is crucial to explore the molecular mechanisms underlying epilepsy inhibition. Inflammation and oxidative stress are important pathophysiological changes in epilepsy that contribute to the development of spontaneous seizures and cognitive deficits. Recently, altered gut microbiota composition was found to be involved in epilepsy, but the underlying mechanism remains unclear. Modulation of the gut microbiota showed a positive impact on the brain by regulating oxidative stress and inflammation. Hence, this study evaluated the effect of modulating gut dysbiosis by treating epileptic rats with prebiotics, probiotics, and synbiotics and investigated the underlying molecular mechanism. Materials and methods: Epileptic rat models were established by injecting 1 µL of kainic acid (KA, 0.4 µg/µL) into the right amygdalae. The rats were divided into Sham, KA, KA+prebiotic (inulin:1 g/kg body weight (bw)/day), KA+probiotics (10 × 109 cfu of each bacteria/kg, bw/day), and KA+synbiotic groups (1:1 mixture of prebiotics and probiotics). Seizures were monitored, and cognitive function was assessed in all rats. Biochemical indicators, including oxidative stress, DNA damage, glutamate levels, and inflammation markers, were also determined. Results: KA-induced status epilepticus (SE) rats exhibited spontaneous seizures and cognitive deficits. This was accompanied by the activation of glial cells, the inflammatory response (IL-1 β, IL-6, and TNF-α), lipid peroxidation (MDA), DNA damage (8-OHdG), the release of glutamate, and a decline in total antioxidant ability (GSH). These changes were alleviated by partial treatment with prebiotics, probiotics, and synbiotics. Conclusion: Modulating gut dysbiosis ameliorates spontaneous seizures and cognitive deficits in rats with KA-induced status epilepticus. The underlying mechanism may potentially involve the inhibition of inflammation and oxidative stress.